High-performance optoelectronic devices based on TeOx nanowires: synthesis, characterization and photodetection - Sui, Jinggao; Lan, Xiang; Zhang, Baihui; Zhong, Mianzeng; Wang, Guang; Cao, Jinhui (Frontiers in Materials, 2024)
Low-dimensional nanomaterials have garnered significant interest for their unique electronic and optical properties, which are essential for advancing next-generation optoelectronic devices. Among these, tellurium suboxide (TeOx)-based nanowires (NWs), with their quasi-one-dimensional (1D) structure, offer distinct advantages in terms of charge transport and light absorption. In this study, we present a comprehensive investigation into the controlled synthesis, structural properties, and optoelectronic performance of TeOx nanowires. Nanowires were synthesized via chemical vapor deposition process and exhibited a high aspect ratio with excellent structural quality, confirmed through Raman spectroscopy, scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The TeOx nanowires demonstrated high crystallinity, smooth surface morphology, and consistent growth across the substrate, making them suitable for scalable device fabrication. The optoelectronic characterization of a fabricated photodetector, based on a single TeOx nanowire, revealed remarkable photoresponsivity and stability across a broad range of light intensities. These findings position TeOx nanowires as promising candidates for future optoelectronic devices such as photodetectors and optical sensors.